31. Histological of Tractus Digestivus of Domestical Catfish (Clarias batracus) - Aliman Irfandi; Cut Dahlia Iskandar; Zainuddin Zainuddin; Dian Masyitha; Fitriani Fitriani; Hamny Hamny; Budianto Panjaitan (Jurnal Medika Veterinaria, 2019)
Domestical catfish is grouped into omnivora, although the fish is tended into carnivora.  The aim of the present study was to investigate histology of alimentary tract of domestical catfish (Clarias batrachus). In order to determine alimentary tract of domestical catfish, oesophagus, gastric and intestines is investigated by Haematoxilin Eosin. Histology exploration was performed each layer of alimentary tract’s wall consist of lamina epithelia, propria, and muscularis mucosa. Collagen connective tissue was developed tunica submucosa. The muscle of tunica muscularis was performed circular and elongated. Dense connective tissue and blood vessels was located in the tunica serosa. Histology exploration revealed has stratified squamous epithelium, mucosit cells, eosinophilic club cells on the lamina epithelia, and taste buds on the lamina propria in oesophagus. Gastric was establised simple prismatic cells, and glands of gastric on the lamina propria. Furthermore intestine was showed villi and goblet cells. There were not showed Brunner and Liberkhun gland. In conclusion, histology of alimentary tract was revealed from tunica mucosa, submucosa, and serosa.